Mobile phone addiction is associated with impaired cognitive reappraisal and expressive suppression of negative emotion - Liu, Jin; Xu, Zhaojun; Zhu, Lili; Xu, Renliying; Jiang, Zhaocai (Frontiers in Psychiatry, 2022)
Previous studies have demonstrated people characterized by mobile phone addiction (MPA) are more prone to emotion regulation difficulties. However, no study has tested the effectiveness of their emotion regulation strategies in experimental conditions. In the present study, by instructing the MPA and control groups to regulate negative emotion through cognitive reappraisal (CR) or expressive suppression (ES), we compared their emotional states in the emotional visual search task after watching a negative emotion evoked video. A multi-factor mixed design of 2(group: MPA/control)×2(emotion regulation strategy: CR/ES)×3(image type: positive expression/negative expression/neutral expression) was conducted. We found the MPA group recognized the negative expression faster than control group after both emotion regulation strategies, indicating ES and CR were both impaired for MPA. The implications of these results were further discussed.